Pioneers, Settlers, Aliens, Exiles: The decolonisation of white identity in Zimbabwe - Fisher, J.L (ANU Press, 2010)
What did the future hold for Rhodesia's white population at the end of a bloody armed conflict fought against settler colonialism? Would there be a place for them in newly independent Zimbabwe? Pioneers, Settlers, Aliens, Exiles sets out the terms offered by Robert Mugabe in 1980 to whites who opted to stay in the country they thought of as their home. The book traces over the next two decades their changing relationship with the country when the post-colonial government revised its symbolic and geographical landscape and reworked codes of membership. Particular attention is paid to colonial memories and white interpellation in the official account of the nation's rebirth and indigene discourses, in view of which their attachment to the place shifted and weakened. As the book describes the whites' trajectory from privileged citizens to persons of disputed membership and contested belonging, it provides valuable background information with regard to the land and governance crises that engulfed Zimbabwe at the start of the twenty-first century.